Effects of dietary supplementation of condensed tannin and calcium nitrate in total mixed rations on long-chain fatty acid metabolism and carcass characteristics of dohne merino lambs - Webb, E.C. (Edward Cottington) (University of Pretoria, 2024)
Dissertation (MSc Agric ( Production Physiology and Product Quality))--University of Pretoria, 2023.